2020
DOI: 10.30935/cedtech/8708
|View full text |Cite
|
Sign up to set email alerts
|

Campus Off, Education On: UAEU Students’ Satisfaction and Attitudes Towards E-Learning and Virtual Classes During COVID-19 Pandemic

Abstract: The study aims at investigating the satisfaction level and attitudes of undergraduate students at United Arab Emirates University towards eLearning and virtual classes in exceptional circumstances of COVID-19 Crisis, in view of five demographic independent variables: students' gender, educational level, residential location, college, and GPA. The researchers adopted and implemented a questionnaire where its validity and reliability for collecting data have been verified. Mean, standard deviations, and one-way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
34
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 17 publications
16
34
2
1
Order By: Relevance
“…For the last research question on whether there is any relationship between academic performances of the Afghan students with their level of satisfaction in online teaching, the analysis of the findings revealed that there was a strong positive correlation between the academic performance of Afghan students and their level of satisfaction with online teaching during the COVID-19 outbreak. This finding is similar to the findings of the studies carried out by (Dhaqane & Afrah, 2016;Malkawi et al, 2021) who found a strong correlation between the academic performance of students and their level of satisfaction. Moreover, when the academic performance of the students has been affected negatively by COVID-19, the level of satisfaction with online teaching can also be highly affected.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For the last research question on whether there is any relationship between academic performances of the Afghan students with their level of satisfaction in online teaching, the analysis of the findings revealed that there was a strong positive correlation between the academic performance of Afghan students and their level of satisfaction with online teaching during the COVID-19 outbreak. This finding is similar to the findings of the studies carried out by (Dhaqane & Afrah, 2016;Malkawi et al, 2021) who found a strong correlation between the academic performance of students and their level of satisfaction. Moreover, when the academic performance of the students has been affected negatively by COVID-19, the level of satisfaction with online teaching can also be highly affected.…”
Section: Discussionsupporting
confidence: 92%
“…Unlike this finding, a study conducted by Abuhassna et al (2020) has reported that students had highly satisfied with online teaching. To consider the overall level of satisfaction with online teaching, several studies have been found in line with the findings of the present study (Aristovnik et al, 2020;Babinčáková & Bernard, 2020;Bauk et al, 2014;Bokayev et al, 2021;Bolliger & Wasilik, 2009;Chen et al, 2020;Durak, 2020;Fatani, 2020 2020; Mahdy, 2020bMahdy, , 2020aMalkawi et al, 2021;Nguyen, 2016;Di Pietro et al, 2020;Shahzadi & Ahmad, 2011;Sharma et al, 2020;Surahman & Sulthoni, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In fact, the preference was to use a hybrid approach that combines both face-to-face with online based education especially for freshman students as well as programs with hands-on components. Furthermore, the results of this study are aligned with other studies as well with respect to the necessity of online education during lockdown period (Coman et al, 2020;Malkawi et al, 2021). In addition, as other studies suggested, courses need to integrate synchronous education meetings as well asynchronous ones for better benefits (Tzivinikou et al, 2020).…”
Section: Discussion Of Resultssupporting
confidence: 86%
“…Recently, the work in (Malkawi et al, 2021) complements our study by considering some aspects of school teachers' perspective towards e-learning across the UAE. Several other studies were conducted to identify challenges during this unprecedented situation (e.g., Basilaia & Kvavadze, 2020;Demuyakor, 2020;García-Morales et al, 2021;Mailizar et al, 2020;Sintema, 2020;Zhou et al, 2020).…”
Section: Related Workmentioning
confidence: 94%